Future changes of El Niño in two global climate models - Meehl, Gerald A.; Teng, Haiyan; Branstator, Grant (Climate Dynamics, 2006)
Idealized forcing experiments with 1% per year CO2 increase to stabilized doubled and quadrupled CO2, twenty-first century transient scenario experiments (SRES scenarios A1B and B1), and stabilized twenty-second century A1B and B1 experiments with two global coupled climate models (PCM and CCSM3) are analyzed for possible future changes of El Niño events. With increased CO2 in the models, there is a reduction of amplitude of El Niño events. This is particularly apparent with larger forcing in the stabilized 4×CO2 experiment in PCM and the stabilized greenhouse gas A1B experiment in CCSM3, where the reduction of amplitude is outside the range of the inherent multi-century variability of El Niño in the control runs of the models and is statistically significant. With moderately increased forcing (stabilized 2×CO2 in PCM and the stabilized B1 experiment in CCSM3), the reduction in amplitude is evident, but it is not significant. The change in El Niño behavior with larger forcing is attributed to the change in base state temperature in the equatorial Pacific, which is similar with increased greenhouse gases (GHGs) in both models. Positive temperature anomalies in and below the thermocline, associated with a reduction of the trade winds, and weakened Pacific Ocean subtropical cells, produce a less intense thermocline, and consequently lower amplitude El Niño events. The previously noted intensification of El Niño tropical precipitation anomalies in a warmer mean base state that applied when there was no appreciable change in El Niño amplitude does not hold in the present study where the El Niño events decrease in magnitude in a future warmer climate. North American surface temperature anomalies associated with El Niño are reduced and become less significant in the future events, with the anomalously deepened Aleutian low in the North Pacific weakened and moved eastward with greater radiative forcing. Part of this is attributed to the smaller amplitude events and thus lower amplitude teleconnections as indicated by ...